2021
DOI: 10.1016/j.radonc.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Seminal vesicle intrafraction motion during the delivery of radiotherapy sessions on a 1.5 T MR-Linac

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…For both groups, even larger outliers as an effect of unstable gas pockets with a tendency to push the prostate can be seen in the anterior and cranial translation direction. Similar effects of gas pockets on prostate intrafraction motion were reported in our previous study on seminal vesicle tracking [23] and in literature [24,25]. Obviously, the present ATP procedure cannot correct for such sudden events.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For both groups, even larger outliers as an effect of unstable gas pockets with a tendency to push the prostate can be seen in the anterior and cranial translation direction. Similar effects of gas pockets on prostate intrafraction motion were reported in our previous study on seminal vesicle tracking [23] and in literature [24,25]. Obviously, the present ATP procedure cannot correct for such sudden events.…”
Section: Discussionsupporting
confidence: 85%
“…In our previous study including 50 patients we found drift to be the major intrafraction motion component in 30% of all fractions and during at least one fraction in 76% of all patients [23]. Intrafraction motion mainly caused by gas pockets was observed in 18% of all fractions and occurred in at least one fraction in 50% of all patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our investigation, we focused exclusively on the residual inter-fraction anatomical variations after bony alignment and did not consider intra-fraction motion. However, several recent studies on cine-MR imaging extensively reported that prostate intrafraction motion could affect the target dose distribution (28,29). These studies concluded that 5-mm PTV margins were adequate to guarantee target coverage even during long-lasting treatments (>10 min).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-fractional changes during radiotherapy delivery have become even more important with current interest in extremely-hypofractionated radiotherapy (i.e., ≤ 3 fractions) with larger fractional doses and therefore longer beam-on times [11] , [12] , [13] . Previously, we have presented intra-fraction motion results in prostate cancer (PCa) [1] , [14] . These results demonstrated that to guarantee target coverage with planning target volume (PTV) margins below 5 mm, workflows that allow intra-fraction adaptation are needed.…”
Section: Introductionmentioning
confidence: 99%